Productive self-advocacy: how Kanye West and Kendrick Lamar communicate Black sovereignty - Sanon, Clarence, author; Marks, Nick, advisor; Chung, Hye Seung, committee member; Pippen, John, committee member (Colorado State University. Libraries, 2022)
Hip-hop culture has been commodified and sold internationally, but it has always been intertwined, intentionally or otherwise, with social change. This thesis seeks to complicate and reimagine the contemporary hip-hop moment. In contrast to scholarship that interrogates and investigates the 1990 and 2000 hip-hop landscape, this thesis moves to the contemporary; particularly, examining the possibility that Kanye West and Kendrick Lamar used their stardom to advocate messages of, what I call, productive self-advocacy. This new term seeks to articulate a shift in advocacy in artists and activists from singular individual civil rights leaders to many individual activists who collectively work together to solve their community's challenges. Productive self-advocacy moves from asking for a seat at the proverbial table to demanding that the Black community create its own. These artists deploy rhetorical strategies to encode messages that advocate for self-dependency and a departure from traditional appeals to the law as well as government agencies. Through this thesis, I hope to expand research on hip-hop and social movements to explore the new era of advocacy from artists and the public.
Keywords: communication; Kanye West; productive self-advocacy; hip-hop; Afrocentricity; Kendrick Lamar